Retention of Intrafibrillar Minerals Improves Resin–Dentin Bond Durability. (November 2022) - Shan, T.; Huang, L.; Tay, F.R.; Gu, L.
The concept of extrafibrillar demineralization involves selective removal of apatite crystallites from the extrafibrillar spaces of mineralized dentin without disturbing the intrafibrillar minerals within collagen. This helps avoiding activation of endogenous proteases and enables air-drying of partially demineralized dentin without causing collapse of completely demineralized collagen matrix that adversely affects resin infiltration. The objective of the present study was to evaluate the potential of quaternized carboxymethyl chitosan (QCMC)–based extrafibrillar demineralization in improving resin–dentin bond durability. Isothermal titration calorimetry indicated that QCMC synthesized by quaternization of O -carboxymethyl chitosan had moderate affinity for Ca 2+ (binding constant: 8.9 × 10 4 M −1 ). Wet and dry bonding with the QCMC-based demineralization produced tensile bond strengths equivalent to the phosphoric acid (H3 PO4 )–based etch-and-rinse technique. Those bond strengths were maintained after thermocycling. Amide I and PO4 3− mappings of QCMC-conditioned dentin were performed with atomic force microscope–infrared spectroscopy (AFM-IR). Whereas H3 PO4 -etched dentin exhibited an extensive reduction in PO4 3− signals corresponding to apatite depletion, QCMC-conditioned dentin showed scattered dark areas and bright PO4 3− streak signals. The latter were consistent with areas identified as collagen fibrils in the amide I mapping and were suggestive of the presence of intrafibrillar minerals in QCMC-conditioned dentin. Young's modulus mapping of QCMC-demineralized dentin obtained by AFM-based amplitude modulation–frequency modulation recorded moduli that were the same order of magnitude as those in mineralized dentin and at least 1 order higher than H3 PO4 -etched dentin. In situ zymography of the gelatinolytic activity within hybrid layers created with QCMC conditioning revealed extremely low signals before and after thermocycling, compared with H3 PO4 -etched dentin for both wet and dry bonding. Confocal laser scanning microscopy identified the antibacterial potential of QCMC against Streptococcus mutans and Enterococcus faecalis biofilms. Taken together, the QCMC-based demineralization retains intrafibrillar minerals, preserves the elastic modulus of collagen fibrils, reduces endogenous proteolytic activity, and inhibits bacteria biofilms to extend dentin bond durability.